Loading ultracold gases in topological Floquet bands: the fate of current and center-of-mass responses. (22nd May 2017) - Dauphin, Alexandre; Tran, Duc-Thanh; Lewenstein, Maciej; Goldman, Nathan
Abstract: Topological band structures can be designed by subjecting lattice systems to time-periodic modulations, as was proposed for irradiated graphene, and recently demonstrated in two-dimensional (2D) ultracold gases and photonic crystals. However, changing the topological nature of Floquet Bloch bands from trivial to non-trivial, by progressively launching the time-modulation, is necessarily accompanied with gap-closing processes: this has important consequences for the loading of particles into a target Floquet band with non-trivial topology, and hence, on the subsequent measurements. In this work, we analyse how such loading sequences can be optimized in view of probing the topology of 2D Floquet bands through transport measurements. In particular, we demonstrate the robustness of center-of-mass responses, as compared to current responses, which present important irregularities due to an interplay between the micro-motion of the drive and inter-band interference effects. The results presented in this work illustrate how probing the center-of-mass displacement of atomic clouds offers a reliable method to detect the topology of Floquet bands, after realistic loading sequences.